Interfacial Acid‐Like Microenvironment and Orbital Modulating Strategy toward Efficient Hydrogen Evolution in Neutral High‐Salinity Wastewater/Seawater - Lina Xu; Wei Li; Kuanchang He; Dongmei Ma; Jinxing Ma; Kui Yang; Abid Ahmad; Faliang Cheng; Sihao Lv; Defeng Xing (Small Structures)
Electrochemical high‐salinity wastewater splitting is a promising technology for green hydrogen (H2) production. However, the kinetics of hydrogen evolution reaction (HER) in neutral media is slow, and the high theoretical potential of oxygen evolution reaction leads to large energy losses. Herein, an iron‐based electrocoagulation‐coupled hydrogen production integrated system (IEHPS) is constructed, which is realized by coupling low‐potential anodic iron oxidation reaction with cathodic HER. The non‐noble metal HxWO3‐Ni catalyst is synthesized by fabricating a proton sponge HxWO3 to achieve an interfacial acid‐like microenvironment and doping it with Ni heteroatom to modulate the 4d orbital of W, thereby weakening the adsorption strength of the W site toward hydrogen. Consequently, the HxWO3 Ni demonstrates remarkable performance characteristics, boasting a mere 131 mV overpotential at 10 mA cm−2 and Tafel slope of 44 mV dec− in neutral media. Operating at an applied voltage of 1.5 V, the IEHPS exhibits a high hydrogen production rate of 235 mL g−1 min−1 in seawater. It achieves nearly complete removal of contaminants like rhodamine B and heavy metal ions within a rapid 8–20 min, with an energy consumption of only 3.7 kWh Nm−3. This study provides a promising pathway for efficient and energy‐saving production of high‐purity hydrogen and effective treatment of high‐salinity wastewater.